1977
DOI: 10.1111/j.1399-0004.1977.tb00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the metabolic defect in Broad‐ß disease (hyperlipoproteinaemia type III)

Abstract: The apoprotein composition of the main lipoprotein fractions (VLDL, LDL‐1, LDL‐2 and HDL) was studied initially in 15 patients with Broad‐β disease. Analytical isoelectric focusing of urea‐soluble apo‐VLDL and apo LDL‐1 demonstrated a variant pattern of the polymorphic Apoprotein E with a deficient Apo E‐III band in all patients. The Apo E‐III deficiency pattern was seen in only six out of 304 hyperlipidaemic controls. These six Apo E‐III deficient controls had characteristic signs of Broad+ disease, and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Thus, apoE plays a major role in the metabolism of chylomicrons, very low density lipoproteins and intermediate density lipoproteins (Sherill et al 1980, Goldstein et al 1983. Subjects with type 111 hyperlipidemia are homozygous for apoE-2 (Utermann et al 1977, Brown et al 1983. Recently, the apoE-4 isoform has been found to be more frequent among hypercholesterolemic subjects (Cumming & Robertson 1984, Utermann et al 1984a).…”
mentioning
confidence: 99%
“…Thus, apoE plays a major role in the metabolism of chylomicrons, very low density lipoproteins and intermediate density lipoproteins (Sherill et al 1980, Goldstein et al 1983. Subjects with type 111 hyperlipidemia are homozygous for apoE-2 (Utermann et al 1977, Brown et al 1983. Recently, the apoE-4 isoform has been found to be more frequent among hypercholesterolemic subjects (Cumming & Robertson 1984, Utermann et al 1984a).…”
mentioning
confidence: 99%
“…This cut-point clearly separated individuals with dysbetalipoproteinemia from other subjects. All probands with dysbetalipoproteinemia, whether hyperlipidemic or not, were found in the groups with E-II/E-I11 ratios >2.95 (Utermann et al 1977b(Utermann et al , c, 1978.…”
Section: Evaluation Of a P O E Phenotypes By Densitometrymentioning
confidence: 99%
“…The three common phenotypes in this system (Apo E-N, Apo E-ND and Apo E-D) are determined by two alleles designated Apo E n and Apo E d (Utermann et al 1977~). Hyperlipidemic individuals with phenotype Apo E-D all have type 111 hyperlipoproteinemia (Utermann et al 1977b); norrnolipidemic subjects with this phenotype have a lipoprotein pattern designated primary dysbetalipoproteinemia (= normolipidemic type 111). We report here on a systematic comparative evaluation of Apo E phenotypes by the new precipitation-I.E.F.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,4 The common variants of apoE were discovered about 40 years ago 8 and their presence was confirmed at the end of 1970s in several studies. [6][7][8][9][10][11][12] In particular, it was reported that, upon two-dimensional gel electrophoretic analysis, apoE from human very-low density lipoprotein (VLDL) of different individuals appears in either one of two complex patterns, designated as class a and b. 13 In 1981, it was demonstrated that the proteins belonging to class b (b-II, b-III, and b-IV) represent homozygosity for three identical APOE gene variants.…”
Section: Introductionmentioning
confidence: 98%